PENGARUH PEMBERIAN TONGKOL JAGUNG DALAM RANSUM TERHADAP PRODUKTIVITAS SAPI POTONG SIMENTAL: THE EFFECT OF GIVING CORN COBS IN THE RATIONAL ON THE PRODUCTIVITY OF SIMMENTAL BEEF CATTLE - Cahyono, Bayu; Purwadi, Purwadi; Wulandari, Eudia Christina (Tropical Animal Science, 2023)
ABSTRACT The aim of this research was to determine the effect of giving corn cobs on the productivity of Simmental beef cattle. The material used in this study were 14 Simmental cattle with an average body weight of 428 ± 16.7 Kg (CV = 3.91%) and an average age - an average of 2 years. The method used was RAL with 2 treatments (P0, P1) with 7 replications. Research parameters are dry matter consumption, crude protein consumption, TDN consumption, daily weight gain, feed conversion, and feed cost per gain. Analysis of research results using the "t test" method with the spss program. The results of the statistical analysis of the research found that the use of corn cobs had a significant effect on dry matter consumption, crude protein and feed cost per gain. The conclusion of this research is that the addition of corn cobs to the ration of simental cattle has a significant effect on the productivity of simental cattle in terms of efficiency and profitability.